Web 2.0 as a tool for market intelligence acquisition in the Malaysian hotel industry - Yap, C. S.; Cheng, Boon Liat *; Choe, K. L. (Lund University, Sweden, 2014)
Introduction: Web 2.0 applications such as social networks, blogs, content aggregators, online forums, and content communities can serve as powerful marketing communication tools for disseminating product information, obtaining feedback from customers, and creating online communities. This study aims to investigate the current state of market intelligence acquisition from various Web 2.0 applications in hotels and to examine the probable relationship between market intelligence practices, environmental turbulence and firm performance. Method: Data were collected from 280 sales and marketing personnel of hotels via self-administered questionnaire survey. Analysis: Descriptive statistics were used to describe the sample and the distribution of responses to each question. Partial least squares path modelling was used to test the reliability and validity of the data, and the hypothesised relationships in the study. Results: This study revealed that the use of Web 2.0 applications for market intelligence acquisition is still low and found a positive relationship between environmental turbulence, market intelligence acquisition and firm performance. Conclusions: This paper concluded that higher perceived environmental turbulence leads to higher extent of market intelligence acquisition, which subsequently leads to enhanced firm performance among the hotels in Malaysia.